Anthropogenic Infection of Domestic Cats With SARS-CoV-2 Alpha Variant B.1.1.7 Lineage in Buenos Aires - Pecora, Andrea; Malacari, Dario Amilcar; Mozgovoj, Marina Valeria; Díaz, María de los Ángeles; Peralta, Andrea Verónica; Cacciabue, Marco; Puebla, Andrea Fabiana; Carusso, Cristian; Mundo, Silvia Leonor; Gonzalez Lopez Ledesma, María Mora; Gamarnik, Andrea Vanesa; Rinaldi, Osvaldo; et al. (Frontiers in Veterinary Science, 2022)
SARS-CoV-2 reverse zoonosis, particularly to domestic animals, and the potential role of infected animals on perpetuating the spread of the disease is an issue of increasing concern. In this report, we identified the natural infection of two cats by SARS-CoV-2 in Argentina. The feline oropharyngeal (OP) and rectal (R) swab samples were processed by RT-qPCR revealing the presence of SARS-CoV-2 genetic material. The owner of the cat had reported SARS-CoV-2 infection. Samples from the owner and the cat were taken and sequenced to define the viral origin. The Alpha variant (B.1.1.7 lineage) was identified, including a unique additional mutation in both the human and feline samples, confirming human-to-cat transmission. This study reinforce the One Health concept and the importance of integrating human, animal and environmental perspectives to promptly address relevant health issues.